Common Fixed Point Theorems of Contractions in Partial Cone Metric Spaces over Nonnormal Cones - Zhilong Li; Shujun Jiang (Abstract and Applied Analysis)
We prove some common fixed point theorems of contractions restricted with variable positive linear bounded mappings in θ-complete partial cone metric spaces over nonnormal cones and present some examples to support the usability of our results.